The Effect of Adding Mg-Zn/Al Hydrotalcite on the Decarboxylation Product of Hydroxy Pelargonate Soap - Ella Melyna; Tirto Prakoso; Tatang Hernas Soerawidjaja (Fluida, 2023)
Pelargonic acid is a by-product of the ozonolysis reaction of oleic acid to azelic acid. Pelargonic acid decarboxylation is the process of removing a carboxyl group (-COO-) from pelargonic acid (C9H18O2) to produce n-octane (C8H18) hydrocarbons, which are the main group of hydrocarbons that make up gasoline. The main parameter in gasoline is the octane number. The octane number of n-octane (C8H18) is 15, which is considered low, while good gasoline is desired to have a high octane number. To convert straight-chain alkanes and alkenes into branched alkanes and alkenes, an isomerization process can be carried out on vapor-cracking products using a solid catalyst. Transition metals and their compounds can be used as catalysts. Transition metals are able to change the oxidation state, create complex compounds, absorb other substances on the metal surface, and activate these substances. The transition metals used in this study are Zn and Al. The stages of the research process were the preparation of Mg-Zn/Al hydrotalcite base, the manufacturing of hydroxy pelargonate soap, and the decarboxylation of hydroxy pelargonate soap. The results of this study found that the highest product gain, namely 64.76%, occurred when Mg-Zn/Al = 5:5:2 hydrotalcite was in 300% excess. The highest product selectivity to 2.16% n-octane occurred in the use of a 300% excess of Mg-Zn/Al = 3:3:2 hydrotalcite. A low Al/Mg/Zn ratio of 2:10 can increase product yield; a high Al/Mg/Zn ratio of 2:6 can increase product selectivity and lower the freezing point.